2016
DOI: 10.14260/jemds/2016/1116
|View full text |Cite
|
Sign up to set email alerts
|

Histomorphological Pattern of Non-Neoplastic and Pre-Neoplastic Lesions of Cervix

Abstract: BACKGROUNDSpecimens from cervix constitute a major contributor of gynaecological tissue received for histomorphological evaluation. Benign lesions presents with varied clinical presentations and age distribution. Lesions such as dysplasia and Cervical Intraepithelial Lesions are a precursor to malignancies which have a high mortality and morbidity among Indian women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…17 Jain et al observed that few patients presented with abnormal vaginal bleeding in his study which excluded malignant cases. 18 Other complaints observed in this study were vaginal discharge, uterovaginal prolapse, and abnormal colposcopy finding which include cervical masses, gross alteration in cervical appearance, and cervical erosion. Few patients had no symptom but had cytology report of high-grade intraepithelial lesion that led them to having cervical biopsy.…”
Section: Discussionmentioning
confidence: 62%
“…17 Jain et al observed that few patients presented with abnormal vaginal bleeding in his study which excluded malignant cases. 18 Other complaints observed in this study were vaginal discharge, uterovaginal prolapse, and abnormal colposcopy finding which include cervical masses, gross alteration in cervical appearance, and cervical erosion. Few patients had no symptom but had cytology report of high-grade intraepithelial lesion that led them to having cervical biopsy.…”
Section: Discussionmentioning
confidence: 62%